Resisting education - Carvalho, J; Koyama, M; Williams, C (Oxford University Press, 2024)
Educational institutions not only build human capital; they also shape culture. We present a model of cultural dynamics produced by cultural transmission through the education system. Groups that are culturally marginalized become economically disadvantaged and exhibit various forms of resistance to education. First, individuals may drop out of education to avoid its cultural content. Second, individuals may invest in other forms of socialization to tune out the cultural content of education. Finally, cultural communities may collectively resist mainstream education by turning out to change curricula or establish their own schools. We show that resistance to education can make it impossible for a policymaker to eliminate alternative cultural traits from the population. In fact, a policymaker may have to moderate the cultural content of education or else face a backlash which increases the spread of alternative cultural traits. Our analysis unifies a growing body of empirical work on the effects of cultural policies and makes new predictions regarding the effect of socializing institutions on cultural dynamics.